IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT BY APLLYING INDEX CARD MATCH STRATEGY - Amelia Sri Rizky Sitepu; Masitowarni Siregar (Universitas Negeri Medan, 2014)
The objective of this study is to find out whether the application of Index Card Match Strategy can improve students’achievement in writing procedure text. This study was conducted by using classroom action research. The subject of this research was the grade elevent students of SMA N 1 Lau Baleng. The research was conducted in two cycles. The first cycle consisted of three meetings and the second cycle consisted of two meetings. The instruments for collecting data used writing test for quantitative data and as the quantitaive data used diary notes, questionnaires sheet, interview and observation sheet. Based on the writing tests result, the students score improved in every test. In orientation test, the mean score was 50,28. In cycle 1 the mean score was 64,96 and the mean score cycle II was 77,35. Based on the diary notes and observation sheet, students shown their progress in learning writing English by the application of Index Card Match Strategy and the classroom action research. Students enjoyed the process of learning writing English concluded from the interview sheet. In line with the data, it was found that the index card match strategy can improve students’achievement in writing pocedure text.